Cenomanian ammonites from northern aquitaine - Moreau, P; Francis, I; Kennedy, W (1983)
Ammonites from the Cenomanian of northern Aquitaine include Neolobites vibrayeanus (d'Orbigny, 1841), Calycoceras (Calycoceras) naviculare (Mantell, 1822), C. cenomanense (d'Archiac, 1846), Pseudocalycoceras cf. dentonense (Moreman, 1942), Eucalycoceras sp., Acanthoceras (Acanthoceras) pseudorenevieri (Spath, 1926), A. (A.) sp. juv. and Metoicoceras geslinianum (d'Orbigny, 1850). These are cosmopolitan taxa, and occur in a Mesogean sequence with a rudistid-larger benthonic foraminifer-dominated fauna, and permit a precise correlation with the boreal ammonite sequences of Sarthe and the Anglo-Paris Basin. © 1983 Academic Press Inc. (London) Ltd.